Psychophysiological study of the concentration period in shooting - Guillot, A.; Collet, C.; Dittmar, A.; Delhomme, G.; Delemer, C.; Vernet-Maury, E. (Journal of Human Movement Studies, 2005)
The time period prior to the trigger pull is considered a preparatory period during which marksmen focus their attention on the target. Autonomic Nervous System (ANS) recording has been shown to reflect mental operations of movement preparation at a peripheral level. Such physiological indicators are considered reliable indicators in studying mental processes. ANS responses during both competition Simulation (concentration and shooting phases) and mental rehearsal can be analysed and compared. Fourteen participants took part in a modern pentathlon shooting competition and a motor imagery session. Five ANS parameters were simultaneously recorded in real time: skin potential, skin resistance, skin temperature, skin blood flow and instantaneous heart rate. Similar ANS response patterns were observed during concentration, shooting and imagery phases. A cardiac deceleration was recorded during both concentration and imagery phases and was related to an increase in focused attention. The earlier this deceleration was initiated, the poorer the shot.